Nano protective membrane coated wheat to resist powdery mildew - Zhang, Huilan; Yuan, Meng; Gao, Yameng; Su, Pengfei; Jia, Huiling; Tang, Caiguo; Meng, He; Wu, Lifang (Frontiers in Plant Science, 2024)
The plant pathogenic fungus Blumeria graminis f. sp. tritici infects wheat and reduces its yield. The policy of reducing fertilizer and biocide use in sustainable agriculture has prompted researchers to develop more green and efficient management strategies. In this study, a novel nanoprotective membrane (kaolin-nano titanium dioxide-liquid paraffin, referred to as KTP) that could effectively prevent powdery mildew of wheat was prepared by using 1 g/L kaolin, 2 g/L nanotitanium dioxide and 8% (v/v) liquid paraffin. The prevention and control effects of KTP spraying in advance in the pot and field experiments were 98.45% and 83.04%, respectively. More importantly, the weight of 1000 grains of wheat pretreated with KTP was 2.56 g higher than that of wheat infected with powdery mildew, significantly improving wheat yield. KTP delayed the germination of powdery mildew spores on the leaf surface, and inhibited the formation of mycelia. In addition, KTP did not affect the growth of wheat or the survival of earthworms. KTP nanoprotective membrane are a green and safe prevention and control materials that are which is expected to be widely used in agriculture to control wheat powdery mildew.